Active damping performance of the KAGRA seismic attenuation system prototype. (May 2016) - Fujii, Yoshinori; Sekiguchi, Takanori; Takahashi, Ryutaro; Aso, Yoichi; Barton, Mark; Arellano, Fabián Erasmo Peña; Shoda, Ayaka; Akutsu, Tomotada; Miyakawa, Osamu; Kamiizumi, Masahiro; Ishizaki, Hideharu; Tatsumi, Daisuke; et al.
Abstract: The Large-scale Cryogenic Gravitational wave Telescope (formerly LCGT now KAGRA) is presently under construction in Japan. This May we assembled a prototype of the seismic attenuation system (SAS) for the beam splitter and the signal recycling mirrors of KAGRA, which we call Type-B SAS, and evaluated its performance at NAOJ (Mitaka, Toyko). We investigated its frequency response, active damping performance, vibration isolation performance and long-term stability both in and out of vacuum. From the frequency response test and the active damping performance test, we confirmed that the SAS worked as we designed and that all mechanical resonances which could disturb lock acquisition and observation are damped within 1 minute, which is required for KAGRA, by the active controls.